2019
DOI: 10.14198/jhse.2020.154.13
|View full text |Cite
|
Sign up to set email alerts
|

Running virtual: The effect of virtual reality on exercise

Abstract: Research has shown that exercise among college aged persons has dropped over recent years (Lindahl, 2015; Sheppard, 2016). Many factors could be contributing to this reduction in exercise including: large workloads, the need to work during school, or perhaps technology use. A number of recent studies are showing the benefits of using virtual reality systems in exercise and are demonstrating that the use of such technology can lead to an increase in the number of young adults engaging in exercise. This study fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 12 publications
7
23
0
1
Order By: Relevance
“…Furthermore, Farrow et al [41] showed that IVR can significantly increase the pleasure of exercising on a cycle ergometer during high-intensity interval training. This is consistent with previous studies which confirmed that stationary cycling in a virtual environment gives users more satisfaction than in conventional conditions [34,42]. This is probably related to the gamification effect [43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, Farrow et al [41] showed that IVR can significantly increase the pleasure of exercising on a cycle ergometer during high-intensity interval training. This is consistent with previous studies which confirmed that stationary cycling in a virtual environment gives users more satisfaction than in conventional conditions [34,42]. This is probably related to the gamification effect [43].…”
Section: Discussionsupporting
confidence: 92%
“…The first attempts are being made to analyze locomotor activity on IVR treadmills [29][30][31][32]. Studies are beginning to examine the exercise load in people using different exercise machines and show that the intensity of physical exercise while playing AVGs in IVR is so high that a beneficial effect on health can be expected [33] and that the PA in IVR can be even more intense than during conventional training sessions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our ndings regarding physical performance are consistent with previous research, indicating that exercise with VR results in superior performance by prolonging exercise duration (Matsangidou et al, 2019;McCLURE & Scho eld, 2019). However, using VR did not increase the physical performance of the aerobic group in the present study, which could be due to the applied VR lm.…”
Section: Discussionsupporting
confidence: 92%
“…The research confirms that VR-enhanced aerobic exercise may prove to be an effective method for improving cognitive function and increasing confidence to navigate real-world scenarios among individuals at risk of cognitive impairment [72]. In an additional similar study, over 50% of participants stated that they preferred the VR condition compared to the traditional workout and claimed that it improved their focus [73]. A review of the literature examining the effects of VR suggested that VR exercise has the potential to exert a positive impact on individuals' physiological, psychological, and rehabilitative outcomes compared with traditional exercise [74].…”
Section: Discussionsupporting
confidence: 55%